MicroRNA-505-5p functions as a tumor suppressor by targeting cyclin-dependent kinase 5 in cervical cancer - Kapora, Elena (Biosci Rep, 2019)
MicroRNAs (miRs) are considered to be tumor suppressors or oncogenes as they regulate cell proliferation, migration, invasion, and differentiation. Recently, microRNA-505 (miR-505) has been reported as being involved in the progression of several human cancers. In the present study, we aim to investigate the expression rate and functional role of miR-505-5p in cervical cancer (CC) to determine its significance regarding the disease’s development. The expression of miR-505-5p and cyclin-dependent kinase 5 (CDK5) in specimens of patients with CC and CC cell lines was examined by quantitative real-time PCR (qRT-PCR) and Western Blot. The relationship between miR-505-5p and CDK5 was verified by luciferase reporter assay. Cell counting kit-8 (CCK-8) assay, Scratch wound healing assay and transwell assay were used to detect the roles of miR-505-5p and CDK5 in CC cell functions. Western Blot was utilized to explore the epithelial–mesenchymal transition (EMT) markers. The result showed that in CC tissues and CC cell lines miR-505-5p was down-regulated while CDK5 level was up-regulated. MiR-505-5p was closely correlated with the metastasis-associated clinicopathological features. Overexpression of miR-505-5p inhibited cell viability, cell metastasis and EMT in CC cells. CDK5 was confirmed as a direct target of miR-505-5p and inverse relationship between them was also observed. Overexpression of CDK5 reduces the inhibitory effects of miR-505-5p in CC. Taken together, these results determine that miR-505-5p is a tumor suppressor miRNA which regulates tumor cell proliferation, migration, and invasion via binding to the functional target CDK5 and demonstrates its potential for future use in the treatment of CC.